Cytogenetic data from remote areas of Amazon: new karyotypes for spiny rats (Rodentia: Echimyidae) - Moreira, Camila Do Nascimento; Dalapicolla, Jeronymo; Yonenaga-Yassuda, Yatiyo; Martins, Cesar [UNESP]; Percequillo, Alexandre Reis (De Gruyter, 2025)
Cytogenetics contributed to our knowledge about the diversity of a wide range of species. In this report, we present the karyotype of 28 specimens of 10 species distributed in four genera of family Echimyidae, collected in the Amazonian Forest. These rodents are between the most diverse groups of the Neotropical region and highlights the importance of obtaining chromosome suspension in field conditions. Several of these karyotypes (Makalata sp. 2n = 68, FNa = 100 or 102; Mesomys sp. 1, 2n = 62, FNa = 73 or 75; Mesomys sp. 2, 2n = 62, FNa = 76 or 78; and Mesomys sp. 3, 2n = 62 and FNa = 64 or 66) differ from those previously reported, suggesting that the cytogenetic diversity of Neotropical rodents is far from being properly described and understood.
Keywords: Amazonian forest; isothrix; makalata; mesomys; proechimys